2000
DOI: 10.1007/s150100070039
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whippelii DNA in Saliva of Patients Without Whipple's Disease

Abstract: Tropheryma whippelii is the causative agent of Whipple's disease, a difficult to diagnose systemic illness. Amplification of part of its 16S ribosomal RNA gene(s) has become a standard diagnostic method because of increased sensitivity as compared to classical histopathological analysis. Recently, we demonstrated the presence of T. whippelii DNA by PCR in duodenal biopsies and/or gastric juice of a considerable fraction of individuals without clinical signs of Whipple's disease. In this follow-up study, saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 13 publications
(21 reference statements)
3
41
0
Order By: Relevance
“…In the future, this MAb will be used in our laboratory prospectively in combination with PCR amplification for the detection of T. whipplei in stool samples. This approach could help to differentiate, contrary to PCR, true digestive Whipple's disease from simple carriage without using an invasive procedure (3,5,18,37).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, this MAb will be used in our laboratory prospectively in combination with PCR amplification for the detection of T. whipplei in stool samples. This approach could help to differentiate, contrary to PCR, true digestive Whipple's disease from simple carriage without using an invasive procedure (3,5,18,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, positive PCR results have been reported on testing small-bowel and saliva specimens from asymptomatic patients (3,4,11). Although these results have not been independently confirmed (8), they have nonetheless led to a poor predictive diagnostic value for these house-made PCR assays that lack of controls.…”
Section: Quantitative Detection Of Tropheryma Whipplei Dna By Real-timentioning
confidence: 99%
“…In addition, recent studies have shown that the spectrum of infections due to T. whipplei is wide and can include localized infection occurring in the absence of small bowel involvement, such as neurological infection, pneumonia, endocarditis, uveitis, and spondylodiscitis (11). In addition, T. whipplei has also been observed in asymptomatic carriers, mainly in fecal and saliva samples (3,10,17). In Europe, the prevalence of this bacterium in fecal samples from the general healthy adult population is estimated to be 1% to 11% (8).…”
mentioning
confidence: 99%